(untitled) (Journal of Economic Research & Business Administration, 2015)
There is a high degree of correlation between the levels of urbanization and socio-economic development of the country. Kazakhstan quickly moved into a number of countries with the average of GNI per capita. But to enter the number 30 top countries in the world we need to overcome the one-sided structure of the economy, the existing social and territorial differences, choose a balanced strategy to develop agglomerations and urban development, industrialization locomotives.